In Vitro and In Vivo Characterization of N-Acetyl-L-Cysteine Loaded Beta-Tricalcium Phosphate Scaffolds - Jang, Yong-Seok; Manivong, Phonelavanh; Kim, Yu-Kyoung; Kim, Kyung-Seon; Lee, Sook-Jeong; Bae, Tae-Sung; Lee, Min-Ho (International Journal of Biomaterials, 2018)
Beta-tricalcium phosphate bioceramics are widely used as bone replacement scaffolds in bone tissue engineering. The purpose of this study is to develop beta-tricalcium phosphate scaffold with the optimum mechanical properties and porosity and to identify the effect of N-acetyl-L-cysteine loaded to beta-tricalcium phosphate scaffold on the enhancement of biocompatibility. The various interconnected porous scaffolds were fabricated using slurries containing various concentrations of beta-tricalcium phosphate and different coating times by replica method using polyurethane foam as a passing material. It was confirmed that the scaffold of 40 w/v% beta-tricalcium phosphate with three coating times had optimum microstructure and mechanical properties for bone tissue engineering application. The various concentration of N-acetyl-L-cysteine was loaded on 40 w/v% beta-tricalcium phosphate scaffold. Scaffold group loaded 5 mM N-acetyl-L-cysteine showed the best viability of MC3T3-E1 preosteoblastic cells in the water-soluble tetrazolium salt assay test.